Acupuncture plus rehabilitation for post-stroke depression: A protocol for systematic review and meta-analysis. Issue 28 (10th July 2020) - Hou, Yonghui; Zhang, Ning; Hao, Jieming; Wang, Xiangzhi; Wen, Zehuai; Luo, Ding; Ning, Baile; Fu, Wenbin; Liu, Ying
Abstract: Background: Post-stroke depression (PSD) is a common stroke complication that is characterized by hopelessness, anxiety, disordered sleep, and lowered responsiveness. Rehabilitation and acupuncture treatments are often combined to treat PSD; however, there has been no meta-analysis on their synergistic effect. Therefore, we aim to perform a systematic review and meta-analysis to estimate the effectiveness of acupuncture and rehabilitation in PSD treatment. Methods: We will search the following electronic databases: PubMed, the Cochrane Library, EMBASE, the China National Knowledge Infrastructure, the Chinese Biomedical Literature Database, China Science and Technology Journal Database, and Wan Fang databases. We will include studies published between the database initiation and May 2020. Two reviewers will separately conduct study selection, data extraction, and risk of bias assessment. Disputes will be settled by consulting a third reviewer. Review Manager Software 5.3 will be employed for this meta-analysis. Results: This systematic review will assess whether acupuncture combined with rehabilitation treatment is more effective than rehabilitation alone in the management of PSD. Conclusion: This systematic review will provide evidence regarding the synergistic effect of acupuncture and rehabilitation treatment for PSD.